Tactical Thirdspace: the physical and virtual spaces of community literacy - Haltiwanger, Talisha, author; Jacobi, Tobi, advisor; Langstraat, Lisa, committee member; Vernon, Irene, committee member (Colorado State University. Libraries, 2013)
Using the lens of Edward Soja's Thirdspace, this thesis investigates the physical and virtual spaces of two community literacy programs. This study makes use of narrative inquiry and presents a thematic analysis of the narratives of two literacy facilitators, and applies Michel de Certeau's framework of strategies and tactics to the narratives, demonstrating a tactical navigation of space within drop-in centers for homeless youth. The tactics used by the facilitators result in the production of a "Tactical" Thirdspace. Additionally, the study includes a dialogic analysis of discourse included in the online spaces of the two literacy programs, which examines the multiple ways in which the organizations and their writers challenges prevailing stereotypes against homeless youth through what Gwendolyn Pough describes as "bringing wreck," as well as the ways in which the discourse presented in the spaces produces and fails to produce Soja's Thirdspace. As in the physical space, the tactical nature of community literacy efforts produces Tactical Thirdspace. The study concludes with an exploration of the possibilities and limitations of Tactical Thirdspace within community literacy work and by arguing for additional spatial analysis of the physical and virtual sites of community literacy.
Keywords: youth; homeless; writing; literacy; community; composition